2021
DOI: 10.1021/acs.joc.1c01770
|View full text |Cite
|
Sign up to set email alerts
|

Fluorine Labeling of ortho-Phenylenes to Facilitate Conformational Analysis

Abstract: 1 H NMR spectroscopy is a powerful tool for the conformational analysis of orthophenylene foldamers in solution. However, as o-phenylenes are integrated into evermore-complex systems, we are reaching the limits of what can be analyzed by 1 Hand 13 C-based NMR techniques. Here, we explore fluorine labeling of o-phenylene oligomers for analysis by 19 F NMR spectroscopy. Two series of fluorinated oligomers have been synthesized. Optimization of monomers for Suzuki coupling enables an efficient stepwise oligomer s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…We focused on o -phenylene hexamers because they are long enough that the oligomer is in slow conformational exchange on the NMR time scale but short enough that the NMR spectra should be tractable even for the expected mixtures of conformers. The fluoro groups were included to help with the NMR analysis, as we have previously shown that 19 F NMR chemical shifts are sensitive to o -phenylene backbone conformations and can be used to detect and quantify the folding populations of different conformers, complementing 1 H- and 13 C-based spectra . The methoxy groups along the backbone were included to ensure solubility; they were not exchanged late in the synthesis for the acetoxy groups used for the imines (Chart a) because it was not found to be necessary to improve folding.…”
Section: Resultsmentioning
confidence: 99%
“…We focused on o -phenylene hexamers because they are long enough that the oligomer is in slow conformational exchange on the NMR time scale but short enough that the NMR spectra should be tractable even for the expected mixtures of conformers. The fluoro groups were included to help with the NMR analysis, as we have previously shown that 19 F NMR chemical shifts are sensitive to o -phenylene backbone conformations and can be used to detect and quantify the folding populations of different conformers, complementing 1 H- and 13 C-based spectra . The methoxy groups along the backbone were included to ensure solubility; they were not exchanged late in the synthesis for the acetoxy groups used for the imines (Chart a) because it was not found to be necessary to improve folding.…”
Section: Resultsmentioning
confidence: 99%